2021
DOI: 10.51628/001c.27687
|View full text |Cite
|
Sign up to set email alerts
|

How do we generalize?

Abstract: Humans and animals are able to generalize or transfer information from previous experience so that they can behave appropriately in novel situations. What mechanisms–computations, representations, and neural systems–give rise to this remarkable ability? The members of this Generative Adversarial Collaboration (GAC) come from a range of academic backgrounds but are all interested in uncovering the mechanisms of generalization. We started out this GAC with the aim of arbitrating between two alternative conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“…All this reasoning is centered on the type of integrative encoding mechanisms identified in the related rodent studies [ 3 , 4 ]—in which related experiences are encoded in overlapping sets of neurons—but the performance of our human participants may have been influenced by multiple integrative and interference processes. Indeed, developing clear operational definitions of integration—and generalization more broadly—has been a theoretical thorn in the side of our field [ 65 ] because multiple mechanisms dictate how memories interact at both the time of encoding and retrieval. Broadly construed, behaviours reflecting memory integration could be supported by three encoding processes [ 37 ]: (1) fusing experiences within one representation, potentially at the cost of idiosyncratic experiential details [ 66 , 67 ], (2) explicitly linking two separately represented experiences [ 68 , 69 ], for example, by building a complex situation model [ 70 ], and (3) separately encoding memories that can later be recombined at the time of retrieval [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…All this reasoning is centered on the type of integrative encoding mechanisms identified in the related rodent studies [ 3 , 4 ]—in which related experiences are encoded in overlapping sets of neurons—but the performance of our human participants may have been influenced by multiple integrative and interference processes. Indeed, developing clear operational definitions of integration—and generalization more broadly—has been a theoretical thorn in the side of our field [ 65 ] because multiple mechanisms dictate how memories interact at both the time of encoding and retrieval. Broadly construed, behaviours reflecting memory integration could be supported by three encoding processes [ 37 ]: (1) fusing experiences within one representation, potentially at the cost of idiosyncratic experiential details [ 66 , 67 ], (2) explicitly linking two separately represented experiences [ 68 , 69 ], for example, by building a complex situation model [ 70 ], and (3) separately encoding memories that can later be recombined at the time of retrieval [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that consolidation processing is not necessary for the effect of reward conditioning on episodic memory generalization. We propose that different types of generalization may not be equally affected by consolidation during sleep [ 31 ]. Precisely, the similarity between the conditioned and the generalization stimuli may determine whether the reward effect on generalization is consolidation-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…If the conditioned and the generalization stimuli are represented in the brain separately (as in an acquired equivalence task), the “offline” state at rest or overnight sleep after conditioning is helpful to integrate or bridge learning experiences together for generalizing or inferencing [ 32 ]. In addition, earlier studies have also proposed a crucial role of sleep in generalization [ 2 , 31 , 33 ]. Conversely, when the difference between conditioned and generalization stimuli is minimal, if the original representation of the conditioned stimuli can be recollected, the representation of the generalization stimuli can also be activated; hence, the consolidation process is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…), is a critical feature of biological agents, and a yet unattainable goal for artificial ones. As reviewed by Taylor and colleagues [1], notwithstanding the many different disciplines that have attempted to define generalization and describe its behavioral, cognitive, and neural underpinning, adjudicating between competing theoretical frameworks (e.g., memory integration vs. on-the-fly inference) is currently impossible. Building on the Authors' observation that progress will come from cross-laboratory, cross-disciplinary collaborations, we here suggest additional lines of empirical research that could pave the way to pivotal insights, namely: multimodal stimulation, naturalistic paradigms, deep sampling, and computational models.…”
mentioning
confidence: 99%
“…Moreover, generalization can operate on representations evoked in absence of any sensory stimulation, by internal, endogenous processes such as self-generated thoughts which only partially overlap with perception [4], thus calling for dedicated experimental paradigms [5]. Ultimately, to fully understand how real-world generalization works we will need to complement the highly controlled paradigms presented by Taylor and colleagues [1] with experimental conditions that are closer to real life's problem-solving situations. According to basic methodology guidelines, the ability of a study to generalize to other contexts depend on its external validity [6].…”
mentioning
confidence: 99%